Application of TIROCA Model at PT SPINDO - Khoirun Nisa Bahri; Nadia Meirani; Popy Rufaidah (International Journal of Applied Business and International Management, 2019)
This paper aims to examine the application of strategic analysis with the TIROCA (Tangible Asset, Intangible Asset, and Organisational Capability) model as a basis to identify the strengths and weaknesses of a company, namely, PT Steel Pipe Industry of Indonesia, Tbk. (PT SPINDO, Tbk.). The company is one of the steel pipe manufacturers in Indonesia. The company has the largest production capacity in Indonesia and has experience in producing various kinds of steel pipes / tubes and various other related products. The company is one of the largest steel pipe manufacturers with the largets production capacity in Indonesia. The paper used a case study research method in order to explore the strategic strengths and weaknesses of the company through its: tangible asset, intangible asset, and organisational capability. The results of the study show the company's superiority come from the following three-resources: (1) tangible resources are derived from the sophistication of machinery and factory equipment; (2) intangible resources are generated from the innovation and creativity of the firm’s HR in creating various products; and (3) organizational capability resources derived from the firm’s competencies and skills in managing product development and the ability to recruit HR.